Sleep health and its related influencing factors in primary and middle school students in Fuzhou: A large multi-center cross-sectional study - Xu, Xingyan; Zheng, Fuhao; Cai, Yingying; Lin, Jie; Zeng, Zhaonan; Wei, Shichao; Wu, Siying (Frontiers in Public Health, 2022)
Background: This current study set out to investigate the status of sleep health in 7-20-year-old students in Fuzhou and explore the related influencing factors of sleep health. Methods: A total of 38467 children and adolescents in Fuzhou were included in the study through a random stratified cluster sampling. Data were collected from May-June 2019, in 18 primary schools and 18 middle schools from 9 Districts, Fuzhou. Children's parents and adolescents of sampled classes were invited to fill a series of questionnaires about the performance of the last 6 months (sociodemographic characteristics, sleep-related lifestyle behaviors and electronic-products usage). Multiple linear regression was carried out to analyze data. Results: Of the total 40,888 questionnaires we released, 38,467 were valid and effective with the response rate was 94.08%. The age of the surveyed participants was 11.85±3.1, including 20,013 boys and 18,454 girls. The multiple linear regression analysis identified factors associated with sleep health (P<0.05): Boy (coef=0.073, 95%CI: 0.030-0.115), age (coef=1.797, 95%CI: 0.224-0.243), key school (coef=2.069, 95%CI: 0.105-0.193), urban (coef=0.096, 95%CI: 0.054-0.139), excessive daytime sleepiness (coef=0.535, 95%CI: 0.432-0.639), unhealthy sleep habits (coef=0.363, 95%CI: 0.307-0.419), eating before sleep (coef=0.578, 95%CI: 0.527-0.630), using electronic products in bedroom (coef=0.074, 95%CI: 0.028-0.121), screen time per day during school (coef=0.260, 95%CI: 0.235-0.284), frequency of using electronics 30 minutes before bedtime (coef=0.150, 95%CI: 0.134-0.166), strained relationship with parents (coef=0.361, 95%CI: 0.270-0.452), strained relationship with peers (coef=0.267, 95%CI: 0.171-0.363), excessive homework or learning (coef=0.189, 95%CI: 0.141-0.237), time for doing homework (coef=0.266, 95%CI: 0.245-0.287) and mood swings frequently (coef=1.174, 95%CI: 1.127-1.221) negatively impact sleep health. sleep alone (coef=-0.204, 95%CI: -0.262–0.147) were the risk factors for sleep health. Furthermore, Mood swings frequently was considered the most influential factor on overall variables. Conclusions: Sleep health is associated with factors covered sociodemographic characteristics, family sleep habits and routine activities before bedtime. Multiple measures should be taken to improve sleep quality in a targeted manner.